Hypothalamic Obesity in Children - BEREKET, ABDULLAH (KARGER, 2015)
Hypothalamic obesity (HyOb) is a severe and rapidly developing form of obesity that was initially described in patients with hypothalamic tumours and surgical damage. However, this definition has now expanded to include obesity developing after a variety of insults to hypothalamic centres, such as infections, infiltrations, trauma, vascular problems, and hydrocephalus in addition to acquired or congenital functional defects in central energy homeostasis. The pathogenetic mechanisms underlying HyOb are complex and multifactorial. Weight gain results from damage to the ventromedial hypothalamus, which may lead to hyperphagia, a low resting metabolic rate, autonomic imbalance, growth hormone, gonadotropin and thyroid-stimulating hormone deficiencies, hypomobility and insomnia. Disruption of leptin signalling and decreased central sympathetic output seem to have a critical role in the development of HyOb. Surgical strategies to preserve hypothalamic integrity are mandatory for the prevention of HyOb in patients with craniopharyngioma or other hypothalamic tumours. At present, there is no standard pharmacological intervention that has been shown to consistently help these complicated patients. In select cases, octreotide seems to be effective when introduced early after the cranial insult. The safety and effectiveness of bariatric surgery in the management of HyOb has also not been well established. A general overview on HyOb with special emphasis on craniopharyngioma and Prader-Willi syndrome is provided in this chapter. (C) 2015 S. Karger AG, Basel
Keywords: PRADER-WILLI-SYNDROME; INDUCED WEIGHT-GAIN; TERM-FOLLOW-UP; BARIATRIC SURGERY; CHILDHOOD CRANIOPHARYNGIOMA; LEPTIN RECEPTOR; ENERGY-BALANCE; DOUBLE-BLIND; FOOD-INTAKE; ADOLESCENTS